The Duality of Design(ing) Successful Projects. Issue 1 (February 2020) - Rylander Eklund, Anna; Simpson, Barbara
Project success is an issue of intense interest to both scholars and project management practitioners, and yet its theoretical elaboration continues to be somewhat under-developed. Responding to this gap between theory and practice, we tease out the dynamics of the design(ing) duality in relation to project management. Our argument is informed by the contrasting management theories of Taylor (design) and Follett (designing), and it is illustrated by drawing on two different experiences of a large Initial Training Network project funded by the European Commission. We suggest that a comprehensive appreciation of project success requires an interweaving of the substantive and processual understandings reflected in the design(ing) duality.